Neoestoicismo español: el Brocense en Correas y Quevedo - Mañas Núñez, Manuel (Cuadernos de Filología Clásica. Estudios Latinos, 2003)
Francisco Sánchez «El Brocense» publishes in Salamanca in 1600 the first Spanish translation with commentaries of Epictetus Manual. The second Spanish translator of the Manual was Gonzalo Correas (Salamanca 1630). Finally, in 1635 Quevedo edits its Epicteto y Phocilides en español, a translation in verse of Epictetus’ Manual. El Brocense» is the introductor of the neostoic movement in Spain and the direct source of Correas and Quevedo.